Recursos genômicos de Eugenia dysenterica (Mart.) DC. - genoma cloroplastidial e transcritoma de referência - Ribeiro, Stela Barros (2021)
Eugenia dysenterica (Mart.) DC., popularly known as cagaiteira, is a native species of the Brazilian Cerrado that has several potential uses, whether as food, medicinal, wood for construction or ornamental. It also has ecological importance for providing food for species of local fauna. Several studies had already characterized the diversity, genetic structure and performance of microevolutionary processes within native populations and a collection of E. dysenterica germplasm have been carried out in recent decades, using mainly molecular markers. The genomic characterization of native plant species, such as cagaiteira, is an important step towards the development of efficient conservation and plant breeding strategies and this has been made possible thanks to the constant advances in sequencing technologies and tools for data analysis. The objective of this study was to assemble and characterize the chloroplast genome, as well as obtain a reference transcriptome for E. dysenterica, using high-throughput sequencing data. For plastome assembly, DNA samples were obtained from adult individual leaves, sequenced using the Illumina MiSeq platform. For the transcriptome assembly, total RNA samples were extracted from leaves and seedlings and sequenced using the Illumina HiSeq 4000 platform. The chloroplast genome of E. dysenterica is 158,560 bp in size and is organized in a quadripartite structure, common for terrestrial plants described in the literature. The chloroplast genome of E. dysenterica contains a total of 112 different genes, including 78 protein-coding genes, 30 transfer RNA genes, and 4 ribosomal RNA genes. A total of 78 SSR regions were identified, of which the majority are mononucleotides with an A/T repeat motif. Most of the identified SSR are located in intergenic regions of the LSC portion of the chloroplast. The estimated mean nucleotide diversity among the E. dysenterica plastome and four other species of the same genus was 0.0064, ranging from 0.0000 to 0.0315. The Ka/Ks substitution rate among these compared species was 0.1907. Phylogenetic analysis confirmed that E. dysenterica is closely related to other Myrtaceae species, with strong bootstrap values (87.7% to 100%). The characterization of the E. dysenterica transcriptome, using the RNAseq approach, is unprecedented among native Cerrado species and allowed the identification of 171,070 transcripts from 43,605 genes, annotated based on different reference databases. In addition, 636,269 putative SNPs were also identified that should be validated in future studies. The information generated in this study constitute important genomic resources for the species, which can be used in the development of efficient strategies for cultivation and conservation of E. dysenterica, in addition to serving as a subsidy for studies with other non-model tree plant species.